2018
DOI: 10.1111/jrh.12328
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers to Prescribing Buprenorphine for the Treatment of Opioid Use Disorder: Recommendations from Rural Physicians

Abstract: Purpose The United States is in the midst of a severe opioid use disorder epidemic. Buprenorphine is an effective office‐based treatment that can be prescribed by physicians, nurse practitioners, and physician assistants with a Drug Enforcement Administration (DEA) waiver. However, many providers report barriers that keep them from either getting a DEA waiver or fully using it. The study team interviewed rural physicians successfully prescribing buprenorphine to identify strategies for overcoming commonly cite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 13 publications
2
81
0
Order By: Relevance
“…28,29 Numerous strategies to overcome diversion concerns have been reported, such as expanding the health care team by developing relationships with dispensing pharmacists. [30][31][32] Educating waivered providers about these strategies may help mitigate the impact of concerns about diversion on providers' decisions to prescribe buprenorphine.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Numerous strategies to overcome diversion concerns have been reported, such as expanding the health care team by developing relationships with dispensing pharmacists. [30][31][32] Educating waivered providers about these strategies may help mitigate the impact of concerns about diversion on providers' decisions to prescribe buprenorphine.…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study of rural buprenorphine-prescribing physicians identified strategies used to overcome barriers to delivering buprenorphine treatment. 34 Concerns about diversion and misuse and not wanting to be perceived as being inconsistent or too lenient in a small community, which could attract patients who may be perceived as potentially taking advantage of the situation, encouraged physicians to establish clear requirements for treatment and included many who required patients to attend some form of psychosocial treatment especially at the beginning of treatment. 34 Despite these challenges, many physicians also reported high satisfaction and fulfillment with respect to delivering this important treatment.…”
Section: Discussionmentioning
confidence: 99%
“…regarded as the specialty with the most extensive OUD training, primary care specialties may have a greater role in bridging access gaps, particularly in rural and urban underserved communities established as health professional shortage areas. [12][13][14] Little is known about provider-level characteristics for outpatient buprenorphine provision reimbursed by any payer model. 15 Although nurse practitioners and physician assistants can also now become DATA-2000 waivered, most states still require physician oversight, especially with controlled substances.…”
mentioning
confidence: 99%